PERMODELAN SPASIAL PENCEMARAN LOGAM BERAT DI SUNGAI BERBEK KAWASAN INDUSTRI SIDOARJO - Listin Fitrianah (Universitas Mulawarman, 2022)
Berbek Industrial Area is the largest industrial area in Sidoarjo Regency. One of the environmental impacts of industrial activities is water quality. One of the water quality is pollution in the sediment. This study aims to map and analyze the pattern of the spatial distribution of cadmium in sediments which can provide information on distribution in the area and the potential impact of lead accumulation on the environment. The samples taken were sediments from rivers in the area of the Berbek industrial area, Waru District, Sidoarjo Regency. The method used is a survey and laboratory tests. The distribution pattern of lead content in the waters was carried out using spatial analysis by the Arcgis 10.1 program kriging interpolation method. The result of pollution with the highest cadmium content was in the Berbek Region, namely 1.36 ppm. The highest distribution of sediment cadmium content is in the Wadungasri area. The Wadungasri area is a dense industrial area.